Animated Short Dialogue Video in English: An Experimental Study on Its Impact on Students' Listening Comprehension - Muhammad Arbain; Irfan Perdana; Nur Hasby (Lembaga Pengembangan Kinerja Dosen, 2024)
This study investigates impact of using short animated English-dialogue videos on Indonesian EFL students’ listening comprehension compared to traditional audio-based instruction. Employing a true experimental pretest–posttest control-group design, the research involved 60 second-year English Language Education (ELE) students from Islamic University of Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, equally divided into experimental and control groups. The experimental group received instruction via animated video dialogues, while the control group used conventional audio dialogues. Listening comprehension was assessed using validated multiple-choice tests administered before and after a two-week instructional period. Descriptive and inferential statistics, including independent- and paired-samples t-tests, were used to analyze the data. Results showed a statistically significant improvement in the experimental group’s performance (t = 4.79, p < .05), while the control group’s gain was not significant (t = 0.85, p > .05). Moreover, the posttest comparison between groups indicated a significant advantage for the experimental group (t = 2.05, p = .04). These findings suggest that animated video-based instruction enhances listening comprehension more effectively than traditional methods, supporting dual-coding and multimedia learning theories.